Analisis pengaruh penerapan aplikasi Quizizz terhadap minat belajar siswa - Kostafani, Emmanuel Ardillan Kostafani; Tien Bayangkhariwati Tacoh, Yuliana (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
This study aims to examine the impact of using the Quizizz application on students’ learning interest in the Information Technology subject at SMK Negeri 3 Salatiga. The research employed a quantitative approach with a quasi-experimental design, involving an experimental class that utilized Quizizz as a learning medium and a control class that used conventional teaching methods. Data on students’ learning interest were collected through questionnaires and analyzed using the Independent Sample T-Test to determine significant differences between the two groups. The findings revealed that students in the experimental class who learned through Quizizz achieved a mean score of 68.96, while those in the control class obtained a mean score of 57.30. The statistical analysis indicated a significant difference between the two groups, suggesting that the use of Quizizz had a positive and measurable effect on enhancing students’ learning interest. The interactive features of Quizizz, such as real-time feedback, gamification elements, and visual engagement, likely contributed to students’ higher motivation and active participation during the learning process. Based on these results, it can be concluded that Quizizz serves as an effective and engaging digital tool to increase students’ enthusiasm for learning Information Technology. It is therefore recommended that educators integrate Quizizz into classroom activities as a complementary interactive learning medium. Future research is encouraged to investigate the application of other digital platforms or compare the effectiveness of different gamified learning tools across various subjects and educational levels.